Implementasi Manajemen Pendidikan Islam sebagai Instrumen Penguatan Budaya Sekolah Islami: Implementation of Islamic Education Management as an Instrument for Strengthening Islamic School Culture - Sudirman Sudirman (Al-Musannif, 2024)
This study aims to examine in depth the implementation of Islamic education management and its effectiveness in strengthening Islamic school culture at Athirah Islamic High School, Bukit Baruga, Makassar City. The research approach used is qualitative descriptive with data collection techniques through in-depth interviews, participatory observations, and documentation studies. The results of the study show that the managerial functions of planning, organizing, implementing, and evaluating are carried out systematically and integrated with Islamic values. Planning of religious programs is prepared through work meetings involving various school parties, while the implementation includes daily religious activities such as congregational prayers, tahfidz, and the habituation of Islamic morals. The organization of religious educators and coaches is carried out professionally with a clear distribution of duties. The evaluation of Islamic education learning is also carried out holistically, covering cognitive, affective, and behavioral aspects of students. Factors supporting implementation include visionary leadership, a religious organizational culture, and the availability of facilities. The obstacles are the difference in the level of teachers' understanding and the influence of outside culture. This research confirms that Islamic education management is an important instrument in shaping a vibrant and sustainable Islamic school culture.